Enzyme‐Modified Hydrogel Coatings with Self‐Cleaning Abilities for Low Fouling PDMS Devices. Issue 12 (1st July 2015) - Zhang, Hongbin; Jackson, John K.; Bian, Chao; Burt, Helen M.; Chiao, Mu
<x xml:space="preserve">Abstract</x> Enzyme‐containing hydrogel coatings with abilities to automatically degrade proteins are developed by covalently binding proteases onto poly(ethylene glycol)/methacrylic acid hydrogel surfaces. Such active coatings can be easily applied to hydrophobic polydimethylsiloxane (PDMS) surfaces to impart long‐term hydrophilicity and self‐cleaning ability, providing an effective and environmentally friendly way to resist protein fouling in the biologically related application of PDMS‐based devices.